CODE-SWITCHING BY CINTA LAURA IN YOU-TUBE CHANNEL NGOBROL SORE SEMAUNYA - NurniKhairita, Martiya; Panobiyasari, Liza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
Language serves as a tool for expressing one's identity within a community or group in addition to serving as a means of communication. Some members of multilingual speech communities may be bilingual or speak more than two languages. An individual who speaks in two languages fluently is considered to code-switch when communicating with others. This study aims to find the type and function of code switching used by Cinta Laura based on YouTube video Ngobrol Sore Semaunya. This research is qualitative research and the theoretical frameworks applied in the study are Poplack’s (1980) three types of code-switching and Appel and Muysken’s (2006) six functions of code-switching. The result shows that there are three types of code switching found, namely inter-sentential code switching, tag switching, and intra-sentential code switching. In addition, there are several functions of code switching which performed by Cinta Laura, namely referential function, expressive function, phatic, metalinguistic, and the last is poetic function